The case for data science in experimental chemistry: examples and recommendations - Yano, Junko; Gaffney, Kelly J.; Gregoire, John; Hung, Linda; Ourmazd, Abbas; Schrier, Joshua; Sethian, James A.; Toma, Francesca M. (Nature reviews. Chemistry, 2022)
The physical sciences community is increasingly taking advantage of the possibilities offered by modern data science to solve problems in experimental chemistry and potentially to change the way we design, conduct and understand results from experiments. Successfully exploiting these opportunities involves considerable challenges. In this Expert Recommendation, we focus on experimental co-design and its importance to experimental chemistry. We provide examples of how data science is changing the way we conduct experiments, and we outline opportunities for further integration of data science and experimental chemistry to advance these fields. Our recommendations include establishing stronger links between chemists and data scientists; developing chemistry-specific data science methods; integrating algorithms, software and hardware to ‘co-design’ chemistry experiments from inception; and combining diverse and disparate data sources into a data network for chemistry research. Modern data science can help to address challenges in experimental chemistry. This Expert Recommendation describes examples of how data science is changing the way we conduct experiments and outlines opportunities for further integration of data science and experimental chemistry to advance these fields.